(untitled) (LEARNing Landscapes, 2011)
The ability to ask questions is the foundation of inquiry learning. While national research standards promote the use of inquiry skills such as questioning, many programs for pre-service teachers do not include training in the development of these skills, leaving teachers and children lacking in this area. A four-step plan is described for assessing inquiry skills by monitoring types of questions employed in the classroom and implementing changes in classroom practices. Results not only reveal that teachers and their students learn to ask more questions, but also that the number of higher order thinking questions actually increases using these methods.